IDENTIFIKASI MISKONSEPSI DAN PENYEBAB MISKONSEPSI MATERI LARUTAN ELEKTROLIT DAN NONELEKTROLIT MENGGUNAKAN FOUR TIER MULTIPLE CHOICE DIAGNOSTIC TEST - Heppy Okmarisa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
AbstractMisconception is a concept that is not according to the concept recognized by the experts. The electrolyte and non-electrolyte solutions material are chemistry materials in senior high school that is always misconception. This research aimed at knowing whether there was or not student misconception, its percentage on electrolyte and non-electrolyte solutions material and the cause of student misconception that was identified by using four-tier multiple choice diagnostic instruments. This research was a descriptive research. The Purposive sampling technique was used in taking the sample. Four-tier diagnostic test, documentation, observation and interview techniques were used for collecting the data. The findings of this research showed that the misconception happened in electrolyte and non-electrolyte solutions material. The analyzed data showed that the average of student understanding levels were as follows: student who understood concept (16%), student who misconceived (28,67%), student who did not understand concept (24%) and student guessing (31,33%). Based on interview conducted to student about the causes of misconception could be stated as follows: the teacher made student hard to understand the material and student did not repeat the material given by teacher, so misconception happened to students. Keywords : Misconception, Four-Tier Diagnostic Test, Electrolyte and Nonelectrolyte Solutions